Kebiasaan Belajar dalam Literasi Matematika Siswa SMP di Masa Pandemi Covid-19 - Adelia Prihartini (Radian Journal: Research and Review in Mathematics Education, 2022)
ABSTRACTThe COVID-19 pandemic has made changes in learning activities in schools, where students are required to be more independent in learning. Learning mathematical literacy still has to be done by students because mathematical literacy is the ability of someone who can formulate, apply, and interpret mathematics in the context of life. This study aims to analyze how the process of learning mathematics literacy for junior high school students during the covid-19 pandemic. The research method used is descriptive qualitative method. The subjects in this study were class VII students of SMPN 1 Karang Bahagia which consisted of 16 students. The instrument used consisted of a literacy questionnaire and interviews. The results of this study will show how students learn mathematical literacy during the pandemic with indicators of study time, learning resources, understanding the context of mathematics, associating a variety of mathematical texts. Keywords: Study habits, Mathematical literacy, during the covid-19 pandemic.